Short-Chain Fatty Acid Propionate Protects From Hypertensive Cardiovascular Damage. Issue 11 (12th March 2019) - Bartolomaeus, Hendrik; Balogh, András; Yakoub, Mina; Homann, Susanne; Markó, Lajos; Höges, Sascha; Tsvetkov, Dmitry; Krannich, Alexander; Wundersitz, Sebastian; Avery, Ellen G.; Haase, Nadine; Kräker, Kristin; et al.
Abstract : Background: Arterial hypertension and its organ sequelae show characteristics of T cell–mediated inflammatory diseases. Experimental anti-inflammatory therapies have been shown to ameliorate hypertensive end-organ damage. Recently, the CANTOS study (Canakinumab Antiinflammatory Thrombosis Outcome Study) targeting interleukin-1β demonstrated that anti-inflammatory therapy reduces cardiovascular risk. The gut microbiome plays a pivotal role in immune homeostasis and cardiovascular health. Short-chain fatty acids (SCFAs) are produced from dietary fiber by gut bacteria and affect host immune homeostasis. Here, we investigated effects of the SCFA propionate in 2 different mouse models of hypertensive cardiovascular damage. Methods: To investigate the effect of SCFAs on hypertensive cardiac damage and atherosclerosis, wild-type NMRI or apolipoprotein E knockout–deficient mice received propionate (200 mmol/L) or control in the drinking water. To induce hypertension, wild-type NMRI mice were infused with angiotensin II (1.44 mg·kg –1 ·d –1 subcutaneous) for 14 days. To accelerate the development of atherosclerosis, apolipoprotein E knockout mice were infused with angiotensin II (0.72 mg·kg –1 ·d –1 subcutaneous) for 28 days. Cardiac damage and atherosclerosis were assessed using histology, echocardiography, in vivo electrophysiology, immunofluorescence, and flow cytometry. Blood pressure was measured by radiotelemetry. Regulatory T cell depletion using PC61 antibody was used to examine the mode of action of propionate. Results: Propionate significantly attenuated cardiac hypertrophy, fibrosis, vascular dysfunction, and hypertension in both models. Susceptibility to cardiac ventricular arrhythmias was significantly reduced in propionate-treated angiotensin II–infused wild-type NMRI mice. Aortic atherosclerotic lesion area was significantly decreased in propionate-treated apolipoprotein E knockout–deficient mice. Systemic inflammation was mitigated by propionate treatment, quantified as a reduction in splenic effector memory T cell frequencies and splenic T helper 17 cells in both models, and a decrease in local cardiac immune cell infiltration in wild-type NMRI mice. Cardioprotective effects of propionate were abrogated in regulatory T cell–depleted angiotensin II–infused mice, suggesting the effect is regulatory T cell–dependent. Conclusions: Our data emphasize an immune-modulatory role of SCFAs and their importance for cardiovascular health. The data suggest that lifestyle modifications leading to augmented SCFA production could be a beneficial nonpharmacological preventive strategy for patients with hypertensive cardiovascular disease. Abstract : Supplemental Digital Content is available in the text.